مقاصد الأسرة في الزمن الرقمي - Tilout, Jamila (Journal of Contemporary Maqasid Studies, 2024)
The Islamic Shari’ah has always accentuated the importance of family throughout an abundance of solid, precise, and purposeful legal texts. Indeed, most Qur’anic rulings revolve around the family as the nucleus that preserves the social and human order. Yet, in the modern era, the emergence of the Internet has contributed to accelerating the process of social transformation, to the point that we are no longer facing simple changes. Still, rather we are facing sudden bursts of alterations on various levels, which affect the nature of social relations in terms of their establishment, enactment, and continuation. Our aim in this paper is to look at the transformations that have affected the maqasid system in modern times, by focusing on the age of digitisation and its impact on human society, and the family in particular. This paper also attempts to focus on the influence of new media on the family relationship system by discussing the transformations in the system of Islamic objectives and values ​​and their critical effects on family cohesion.